2013
DOI: 10.1017/s002221511200326x
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation after selective vestibular nerve section

Abstract: To our knowledge, this is the first reported case of cochlear implantation carried out after selective vestibular nerve section. Given recent advances in cochlear implantation, this case indicates that it is essential to make every effort to spare the cochlear nerve if vestibular nerve section is required. If hearing loss occurs after vestibular nerve section, magnetic resonance imaging should be undertaken to establish whether the cochlear nerve is intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Few studies have investigated speech perception outcomes after cochlear implantation in MD; in general, outcomes are favorable and compare similarly to those reported in the non‐MD adult population 15–17 . Other studies have also investigated the use of cochlear implantation in MD concomitant with other surgical procedures for vertigo control 18–23 . However, to our knowledge, no study has reported acoustic hearing preservation outcomes after cochlear implantation in MD.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Few studies have investigated speech perception outcomes after cochlear implantation in MD; in general, outcomes are favorable and compare similarly to those reported in the non‐MD adult population 15–17 . Other studies have also investigated the use of cochlear implantation in MD concomitant with other surgical procedures for vertigo control 18–23 . However, to our knowledge, no study has reported acoustic hearing preservation outcomes after cochlear implantation in MD.…”
Section: Introductionmentioning
confidence: 80%
“…[15][16][17] Other studies have also investigated the use of cochlear implantation in MD concomitant with other surgical procedures for vertigo control. [18][19][20][21][22][23] However, to our knowledge, no study has reported acoustic hearing preservation outcomes after cochlear implantation in MD. As the indications for cochlear implantation have expanded to include patients with greater degrees of residual hearing, this has relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Of 37 studies included, 32 (86.5%) studies were full manuscripts [8][9][10][11][12][13] and five (13.5%) were conference abstracts. [43][44][45][46][47] 21 (56.8%) papers were case series (more than one patient), [19][20][21][22][25][26][27][28][29][30]36,37,40,[43][44][45][46][47] 11 (29.7%) were case reports (one patient), 23,24,[30][31][32][33][34][35]38,39,41,42 and five (13.5%) were case-control studies (one or more comparison groups). [8][9][10][11][12] Twenty-five (67.6%) studies were based internationally and 12 (32.4%) studies were based in the United States (Table I).…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Radiological: Magnetic Resonance Imaging (MRI) should be done to exclude retrocochlear pathology especially in unilateral MD with asymmetric sensorineural hearing loss; MRI also is beneficial in evaluating cochlear nerve integrity especially in patients who had undergone vestibular nerve section. Finally, MRI could provide us with some information regarding cochlear ossification or fibrosis together with Computerized Tomography (CT) [15].…”
Section: Pre-operative Evaluationmentioning
confidence: 99%